A pumping condition for regular sets. - Varricchio, Stefano
We prove that a language of a finitely generated free monoid is regular if and only if it satisfies the positive block pumping property. This gives a positive answer to a problem posed by Ehrenfeucht, Parikh and Rozenberg.
Keywords: Automata theory; Regular languages; Pumping conditions